Working time : tendencies and emerging issues - Bosch, Gerhard (1999)
Outlines the ILO Conventions and Recommendations concerned with working time. Analyzes the major trends in the changes in working time and of the forces driving them. Summarizes the conditions in which working time reductions are likely to have a positive effect on employment.